Assessment of asthenic and anxiety disorders in patients with COVID-19 - Runcheva, K. A.; Kozyolkin, O. A.; Medvedkova, S. O.; Рунчева, Катерина Андріївна; Козьолкін, Олександр Анатолійович; Мєдвєдкова, Світлана Олександрівна (Košice : Scholarly Publisher ICSSH, 2023)
Aim of the research: to analyze and evaluate the features of asthenic and anxiety disorders in patients with COVID-19.
Keywords: тези доповідей